Computing Systems with a Reconfigurable (Programmable) Architecture - Палагин, А. В.; Опанасенко, В. Н.; Сахарин, В. Г. (Problems of Informatization and Control, 2004)
Principles of design of PLD-based computing systems with reconfigurable architecture are considered. This systems are used for reconfigurable data processing. The principles of organization PLD-based reconfigurable of systems, which are represented by combination of fixed and variable hardware, are considered. The variable hardware are contain the mother board, modules of the extension and mezzanine card. The structural organization the reconfigurable processor is offered. The primary goals in area «Reconfigurable Computing» are determined